Controlled Release of Flurbiprofen from 3D-Printed and Supercritical Carbon Dioxide Processed Methacrylate-Based Polymer - Truc T. Ngo; Jae D. Kim (MDPI AG, 2023)
The ability to engineer and predict drug release behavior during treatment is critical to the design and implementation of effective drug delivery systems. In this study, a drug delivery system consisting of a methacrylate-based polymer and flurbiprofen was studied, and its release profile in a controlled phosphate-buffered saline solution was characterized. The polymer, which was 3D printed and processed in supercritical carbon dioxide under different temperature and pressure settings, showed sustained drug release over a prolonged period. A computer algorithm was used to determine the drug release time duration before reaching steady state and the maximum drug release at steady state. Several empirical models were applied to fit the release kinetic data to gain information about the drug release mechanism. The diffusion coefficients for each system were also estimated using Fick's law. Based on the results, the influence of supercritical carbon dioxide processing conditions on the diffusion behavior is interpreted, providing insights into the effective and tunable design of drug delivery systems for targeted treatment specifications.